Exploring conformational transitions and free-energy profiles of proton-coupled oligopeptide transporters - Batista, MRB; Watts, A; Costa-Filho, AJ (American Chemical Society, 2019)
Proteins involved in peptide uptake and transport belong to the proton-coupled oligopeptide transporter (POT) family. Crystal structures of POT family members reveal a common fold consisting of two domains of six transmembrane α helices that come together to form a "V" shaped transporter with a central substrate binding site. Proton-coupled oligopeptide transporters operate through an alternate access mechanism, where the membrane transporter undergoes global conformational changes, alternating between inward-facing (IF), outward-facing (OF), and occluded (OC) states. Conformational transitions are promoted by proton and ligand binding; however, due to the absence of crystallographic models of the outward-open state, the role of H+ and ligands is still not fully understood. To provide a comprehensive picture of the POT conformational equilibrium, conventional and enhanced sampling molecular dynamics simulations of PepTst in the presence or absence of ligand and protonation were performed. Free-energy profiles of the conformational variability of PepTst were obtained from microseconds of adaptive biasing force (ABF) simulations. Our results reveal that both proton and ligand significantly change the conformational free-energy landscape. In the absence of ligand and protonation, only transitions involving IF and OC states are allowed. After protonation of the residue Glu300, the wider free-energy well for Glu300 protonated PepTst indicates a greater conformational variability relative to the apo system, and OF conformations became accessible. For the Glu300 protonated Holo-PepTst, the presence of a second free-energy minimum suggests that OF conformations are not only accessible, but also stable. The differences in the free-energy profiles demonstrate that transitions toward outward-facing conformation occur only after protonation, which is likely the first step in the mechanism of peptide transport. Our extensive ABF simulations provide a fully atomic description of all states of the transport process, offering a model for the alternating access mechanism and how protonation and ligand control the conformational changes.